Análisis técnico y de discurso del programa Educa TV durante la emergencia sanitaria, período abril- junio 2020 - Sánchez Jimbo, Camila Alejandra (2021)
This paper analyzes the audiovisual and discourse narrative of the Educa Tv program and its contribution during the health crisis in the education of Ecuadorian children from public institutions during the Covid-19 pandemic. It also raises how the audiovisual story of this television program is built from an educational point of view, and how its narrative content is constructed, influencing the message that is to be transmitted to the audience to which it isdirected. In this way, it is analyzed what methods have been used to reach college students who do not have Internet in Ecuador in Covid-19 and if this has been a feasible, effective and beneficial audiovisual methodology to reach viewers in this pandemic period. Finally, with the information collected, provide a source of information and knowledge for anyone who wants to clear up doubts about this research topic, and it may be useful to the Ecuadorian educational community to continue developing audiovisual products in order to teach and train in this television mode. In this study we used a mixed methodology, that is, the use of a qualitative method where interviews with certain primary education professionals, psychologists and pedagogues specialized in the school education sector and experts in audiovisual content prevailed, in addition to conducting through non-participant observation files, an exhaustive analysis of Educa Tv's programming in its discourse and narrative, in this period of pandemic. In order to corroborate the knowledge of this television channel and its effectiveness in its transmission of educational content, a quantitative methodology was used, with the use of surveys of parents who used this television channel as an educational tool (Educa Tv), for the training of their children in the time of Covid-19, unable to have Internet at home, to be able to use other virtual platforms as teaching resources for their children.